Answer:
-30/58 & -45/87
Step-by-step explanation:
The first answer is just multiplying the original by 2.
The second one is being multiplied by 3.
The multiplicated moves DO NOT CHANGE THE VALUE OF THE ORIGINAL FRACTION, meaning that they are equivalent. :))
Answer:
6
Step-by-step explanation:
pls brainliest
9/2=4.5
27/4.5=6
Answer:
1,911
Step-by-step example
3 x 7
3 x 30
3 x 600
then add it all up to get the 1,911
Answer:
2 seconds
Step-by-step explanation:
Given
h = - 32t² + 64t
When the frisbee lands the height h = 0, that is
- 32t² + 64t = 0 ( multiply through by - 1 )
32t² - 64t = 0 ← factor out 32t from each term
32t(t - 2) = 0
Equate each factor to zero and solve for t
32t = 0 ⇒ t = 0
t - 2 = 0 ⇒ t = 2
t = 0 represents when the frisbee was thrown
and t = 2 when it lands
Hence it takes 2 seconds for the frisbee to land.
Answer: (0,-1/2)
Step-by-step explanation:
Edge :-)